Hungarian Monitoring, 21 January 1988 . [Magyar rádiófigyelő], 1988. január 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Palestinian riots - Evaluation of Shevardnadze's negotiations in Bonn - Soviet Minister of Foreign Affairs in Madrid - Sejm, Warsaw: budget adjustments - Gábor Nagy Deputy Minister of Foreign Affairs in South Africa Domestic Affairs: - International press conference of Hungarian, Italian and Finnish left-wing parties: a joint appeal for strengthening European security and peace - Parliamentary Youth and Sport Committee: inaugural meeting - movement to save the 'Szársomlyó' hill conservation area - Survey by the State Employment Agency on job searching Külpolitika: - Palesztin lázadások - Sevardnadze bonni tárgyalásának értékelése - Madridban a szovjet külügyminiszter - Varsó, Szejm: költségvetési kiigazítások - Nagy Gábor külügyminiszter helyettes Dél-Afrikában Belpolitika: - Magyar, olasz és finn baloldali pártok nemzetközi sajtó konferenciájának közös felhívása - Az Ifjúsági és Sportbizottság alakuló ülése - Mozgalom a Szársomlyó megmentésére - Az Állami Foglalkoztatási Hivatal felmérése a munkahely keresésről